(3cJGH GdWHjYI GdNGeSIs - (3LGHQ Hf MjGf Hf YHO Gddg Gdchaj, CHh ehSi, J (B200 (3g` s
(3ChdgG (B:s
(3QH GYf HgOGjJc GdMeO ddg hHg fSJYjf ajfHZi Cf JYde EfG bO PcQfG ai cJHfG hdcd hGMO ai LejY GdGTjGA hCMOK MGOKkG dG ai GdbGYOI hdG ai GdeMehd YdjgG s
(3BNQgG (B:s
(3BNQ GdehLhO efg bhdg (B: (3agPG LejY eG ai Pdc hcGf ai gPg GdeSCdI hPdc Efc GPG VQHJ GdLhHQ GdChd ai JSYI cGf NWC hZPG VQHJg ai YTQI cGf UhGHkG hPdc CehQ GdWdSeGJ hGdYLGjH GdJi dG JfaP s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGefs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
(3ShQjG (B(9318) s
Keywords: (3GdadSaI hGdefWbs